Shakespeare and laughter : a cultural history - Ghose, Indira (Manchester University Press, 2008)
This book examines laughter in the Shakespearean theatre, in the context of a cultural history of early modern laughter. Aimed at an informed readership as well as graduate students and scholars in the field of Shakespeare studies, it is the first study to focus specifically on laughter, not comedy. It looks at various strands of the early modern discourse on laughter, ranging from medical treatises and courtesy manuals to Puritan tracts and jestbook literature. It argues that few cultural phenomena have undergone as radical a change in meaning as laughter. Laughter became bound up with questio.